Nighttime evaporative demand induces plasticity in leaf and root hydraulic traits. Issue 4 (24th June 2016) - Claverie, Elodie; Schoppach, Rémy; Sadok, Walid
Abstract : Increasing evidence suggests that nocturnal transpiration rate (TRN ) is a non‐negligible contributor to global water cycles. Short‐term variation in nocturnal vapor pressure deficit (VPDN ) has been suggested to be a key environmental variable influencing TRN . However, the long‐term effects of VPDN on plant growth and development remain unknown, despite recent evidence documenting long‐term effects of daytime VPD on plant anatomy, growth and productivity. Here we hypothesized that plant anatomical and functional traits influencing leaf and root hydraulics could be influenced by long‐term exposure to VPDN . A total of 23 leaf and root traits were examined on four wheat ( Triticum aestivum ) genotypes, which were subjected to two long‐term (30 day long) growth experiments where daytime VPD and daytime/nighttime temperature regimes were kept identical, with variation only stemming from VPDN, imposed at two levels (0.4 and 1.4 kPa). The VPDN treatment did not influence phenology, leaf areas, dry weights, number of tillers or their dry weights, consistently with a drought and temperature‐independent treatment. In contrast, vein densities, adaxial stomata densities, TRN and cuticular TR, were strongly increased following exposure to high VPDN . Simultaneously, whole‐root system xylem sap exudation and seminal root endodermis thickness were decreased, hypothetically indicating a change in root hydraulic properties. Overall these results suggest that plants 'sense' and adapt to variations in VPDN conditions over developmental scales by optimizing both leaf and root hydraulics.